The mechanism and clinical application of DNA damage repair inhibitors combined with immune checkpoint inhibitors in the treatment of urologic cancer - Xie, Deqian; Jiang, Bowen; Wang, Shijin; Wang, Qifei; Wu, Guangzhen (Frontiers in Cell and Developmental Biology, 2023)
Urologic cancers such as kidney, bladder, prostate, and uroepithelial cancers have recently become a considerable global health burden, and the response to immunotherapy is limited due to immune escape and immune resistance. Therefore, it is crucial to find appropriate and effective combination therapies to improve the sensitivity of patients to immunotherapy. DNA damage repair inhibitors can enhance the immunogenicity of tumor cells by increasing tumor mutational burden and neoantigen expression, activating immune-related signaling pathways, regulating PD-L1 expression, and reversing the immunosuppressive tumor microenvironment to activate the immune system and enhance the efficacy of immunotherapy. Based on promising experimental results from preclinical studies, many clinical trials combining DNA damage repair inhibitors (e.g., PARP inhibitors and ATR inhibitors) with immune checkpoint inhibitors (e.g., PD-1/PD-L1 inhibitors) are underway in patients with urologic cancers. Results from several clinical trials have shown that the combination of DNA damage repair inhibitors with immune checkpoint inhibitors can improve objective rates, progression-free survival, and overall survival (OS) in patients with urologic tumors, especially in patients with defective DNA damage repair genes or a high mutational load. In this review, we present the results of preclinical and clinical trials of different DNA damage repair inhibitors in combination with immune checkpoint inhibitors in urologic cancers and summarize the potential mechanism of action of the combination therapy. Finally, we also discuss the challenges of dose toxicity, biomarker selection, drug tolerance, drug interactions in the treatment of urologic tumors with this combination therapy and look into the future direction of this combination therapy.